Exploration of Ethnomathematics in Traditional Houses of Papuan People - Iyam Maryati; Muhammad Sahdam Darmawan; Irena Puji Luritawaty (Universitas Suryakancana, 2025)
Ethnomathematics serves as a bridge between history and culture with mathematics, playing a crucial role in recognizing that various cultural activities lead to different mathematical concepts. This study aims to describe the historical, philosophical, and mathematical concepts embedded in traditional Papuan houses, including Honai, Kaki Seribu, Rumah Pohon, and Rumsram. The research was conducted at the Papua Ethnic House Tourism and Cultural Park using a qualitative descriptive research method based on ethnography. Data were obtained through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and data verification techniques. The results showed that traditional Papuan houses integrate mathematical concepts in their structure and design, such as: (1) The Honai house adopts a cylindrical and conical shape for space efficiency and durability; (2) The Kaki Seribu house highlights symmetrical patterns in its numerous supporting pillars, reflecting adaptation to the surrounding environment; (3) The Rumah Pohon applies principles of proportion and stability to ensure safety from external threats; (4) The Rumsram house represents the Biak people's connection to maritime culture while demonstrating geometric principles in its trapezoidal and rectangular structures. In addition to mathematical aspects, traditional Papuan houses contain philosophical and historical values that strengthen local cultural identity. Further research will focus on developing and testing Papuan culture-based mathematics learning models. For example, creating didactic designs that use the Honai House concept to teach geometric shapes (cylinders and cones) or the Thousand-Legged House to teach symmetry and patterns. The effectiveness of these models in enhancing student understanding and interest could be the focus of testing. Practical applications include creating textbooks, modules, learning videos, or even interactive apps that showcase traditional Papuan houses as a medium for learning geometry, patterns, and measurement.